Endogenous beta‐galactosidase activity marks a TREM2‐expressing Kupffer cell population in injured livers of Lgr5‐LacZ and wild‐type mice. Issue 5 (28th November 2019) - Klaas, Mariliis; Mäemets‐Allas, Kristina; Lõhmussaar, Kadi; Tooming, Mikk; Viil, Janeli; Jaks, Viljar
Abstract : Lgr5‐LacZ mice harbor the Escherichia coli LacZ gene encoding β‐galactosidase (β‐gal) under the control of the Lgr5 promoter, a stem/progenitor cell marker. In injured livers of Lgr5‐LacZ mice, cells expressing β‐galactosidase (β‐gal) are considered as potential bipotent liver progenitors; however, their origin and identity remain unknown. Unexpectedly, using lineage tracing, we demonstrate that the β‐gal + cells do not originate from liver parenchymal cells. Instead, β‐gal + cells, isolated from injured livers of both Lgr5‐LacZ and wild‐type mice, are positive for markers of Kupffer cells, liver‐resident macrophages. The β‐gal expression in these cells is a result of elevated expression of the endogenous beta‐galactosidase Glb1. In injured livers of Lgr5‐LacZ mice, bacterial β‐gal expression is very low, suggesting transgene silencing. The gene expression profile of the β‐gal + Kupffer cells from injured livers suggests a role in liver regeneration. Abstract :